Effects of the Ductility Capacity on the Seismic Performance of Cross-Laminated Timber Structures Equipped with Frictional Isolators - Gaspar Auad; Bastián Valdés; Víctor Contreras; José Colombo; José Almazán (Buildings)
In developing countries with high seismic activity, a need exists to construct resilient infrastructure and reduce the housing deficit. Industrialized timber construction and the implementation of seismic isolation interfaces may represent a good alternative to respond to these demands. This paper studies the feasibility of constructing cross-laminated timber (CLT) buildings equipped with frictional pendulum bearings in Chile or similar highly seismic regions. The first part of this study shows a first-order approach for modeling the highly nonlinear behavior of CLT walls using a Smooth Hysteretic Model (SHM). An equivalent model of a base-isolated building was developed using the SHM as well as a physical model of the Friction Pendulum System in order to assess the seismic performance of CLT buildings with frictional isolators. The second part of this research presents and discusses the results of a broad parametric analysis concerning the seismic performance of base-isolated CLT buildings. The seismic assessment was carried out by deriving fragility curves and including the uncertainty linked to the seismic input and the friction coefficient of the isolation system. Constructing lateral resistant systems based on CLT walls presents a feasible alternative for buildings in high seismic hazard areas. Excellent seismic performance is achieved if the superstructure’s is designed with a reduction factor of 1, or if the superstructure’s fundamental period ranges from 0.6 to 0.9 s and is designed with a reduction factor of 2 and ductility capacity of 6 or more. An excellent seismic performance can be obtained for larger reduction factor values if the superstructure has middle to high maximum ductility capacity.